Answer:
The answer is C
Explanation:
Use the method of elimination
First rearrange the first equation to look like the second
![2x + 3y = 17 \\ 4x + 6y = 34 \\ - 4x - 6y = - 34](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7ilifxe5u77ws45usp6k2jm2lhaxjhficq.png)
Next add the two equations together eliminating the y term.
![- 4x - 6y = - 34 \\ 3x + 6y = 30 \\ \\ - x = - 4 \\ x = 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vpc6nlolst9ofkv0swbg5xwrvp1ircprq0.png)
There's only one answer with x = 4 so you're done. To go further, substitute x = 4 into the second equation and solve for y
![3x + 6y = 30 \\ 3 * 4 + 6y = 30 \\ 12 + 6y = 30 \\ 6y = 18 \\ y = 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3dandv2wl00ah6731i01h3h1dci24kc3iz.png)